Gaining deeper insight into aroma perception: An integrative study of the oral processing of breads with different structures. (February 2017) - Jourdren, S.; Saint-Eve, A.; Pollet, B.; Panouillé, M.; Lejeune, P.; Guichard, E.; Déléris, I.; Souchon, I.
Abstract: The objective of this study was to investigate for the first time the influence of bread structure, volatile compounds, and oral processing on aroma perception. 3 types of French baguette were created using the same raw ingredients but different bread-making processes; they consequently varied in their crumb and crust structures. We characterized the initial volatile profiles of two bread structural subtypes—namely bread crumb and bread crumb with crust—using proton transfer reaction–mass spectrometry (PTR–MS) headspace analysis. Three types of bread were characterized by thirty-nine ion fragments from m / z 45 to 139. We then conducted a study in which 8 participants scored aroma attribute intensities for the different bread types and subtypes at 3 key stages of oral processing (10, 40, and 100% of individual swallowing time). At these 3 time points, we collected boli from the participants and characterized their volatile profiles using PTR–MS headspace analysis. The results suggest saliva addition dilutes volatile compounds, reducing volatile release during oral processing. Thus, a bread with high porosity and high hydration capacity was characterized by a low volatile release above boli. We examined the relationships between 4 aroma attributes of bread crumb with crust and 24 discriminatory fragment ions found in boli headspace. This study demonstrated for the first time that the perceived aroma of crumb with crust was influenced more by volatile profiles than by crumb texture. It thus contributes to our understanding of aroma perception dynamics and the mechanisms driving volatile release during oral processing in bread. Graphical abstract: Highlights: Sensory and chemical analyses were conducted on 3 structurally distinct breads and their boli. Volatile profiles above bread boli, analyzed with PTR-MS, varied highly across oral processing. Whatever the crumb structure, the crust brought high variability in volatile profiles and aroma. The study originality was to quantify the variations of perceived aroma across bread consumption. Perceived aroma of crumb with crust was influenced more by volatile profiles than by food texture.